Burden of diseases and injuries attributable to risk factors in the European Union in 2019. (20th October 2021) - Vasco Santos, J; Padron Monedero, A; Kocbach Bolling, A; Bikbov, B; Unim, B; Grad, DA; Plass, D; Fischer, F; Violante, FS; Sulo, G; Ngwa, CH; Noguer-Zambrano, I; et al.
Abstract: Background: In addition to information on mortality and morbidity from diseases and injuries, it is important to identify the attributable burden of risk factors to allow for health planning and prioritization. Methods: For the whole EU and each country, using estimates and 95% uncertainty intervals from the GBD 2019 study, we report attributable (all-cause and by level 2 risk factors) age-standardized death and DALY rates, as well as summary exposure values (SEV). We evaluate trends by comparing estimates for the year 2019 with those for the year 2010. Results: Age-standardized death and DALY rates attributable to risk factors declined by 10.7% (95%UI 13.8%-7.6%) and 9.1% (95%UI 12.0%-6.3%), between 2010 and 2019 in the EU. While there was a decreasing trend for both age-standardized death and DALY rates for almost all risk factors, some showed an increasing trend on SEV, including low physical activity and intimate partner violence. Conclusions: Despite the improvement of health metrics attributable to risk factors, several modifiable behavioral and metabolic risk factors remain unchanged over the years. It is crucial to ensure a swift implementation of evidence-based policies and interventions in EU member states to achieve the targets of the Sustainable Development Goals.